2022
DOI: 10.1101/2022.12.07.519473
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of sex and physical activity on the local immune response to muscle pain

Abstract: Induction of muscle pain triggers a local immune response to produce pain and this mechanism may be sex and activity level dependent. The purpose of this study was to measure the immune system response in the muscle following induction of pain in sedentary and physically active mice. Muscle pain was produced via an activity-induced pain model using acidic saline combined with fatiguing muscle contractions. Prior to induction of muscle pain, mice (C57/BL6) were sedentary or physically active (24hr access to run… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…Consistent with the role of hormones in modulating pain, we have shown that testosterone protects against the development of widespread pain in the activity-induced pain model [78], with orchiectomy producing widespread pain similar to females and testosterone producing unilateral pain similar to males. Further, we have shown female-specific mechanisms of pain in the activity-induced pain model where there was activation of the antigen processing and presentation pathway in the muscle, and blockade of MHC II attenuated development of muscle hyperalgesia [79]. Centrally, females but not males, also have greater serotonin transporter immunoreactivity in the nucleus raphe magnus [78].…”
Section: Sex-specific Differences In the Activity-induced Muscle Painmentioning
confidence: 77%
“…Consistent with the role of hormones in modulating pain, we have shown that testosterone protects against the development of widespread pain in the activity-induced pain model [78], with orchiectomy producing widespread pain similar to females and testosterone producing unilateral pain similar to males. Further, we have shown female-specific mechanisms of pain in the activity-induced pain model where there was activation of the antigen processing and presentation pathway in the muscle, and blockade of MHC II attenuated development of muscle hyperalgesia [79]. Centrally, females but not males, also have greater serotonin transporter immunoreactivity in the nucleus raphe magnus [78].…”
Section: Sex-specific Differences In the Activity-induced Muscle Painmentioning
confidence: 77%
“…10,16 Several reports suggested that CD44 activation in macrophages by HMWH can suppress the release of pronociceptive cytokines from tissue-infiltrating macrophages in rodents. 19,22 Furthermore, macrophages have been widely reported to be involved in the development of musculoskeletal pain 11,12,14,18 and have been specifically implicated in muscle pain development as a consequence of extracellular membrane hyaluronan disruption by hyaluronidase administration. 18 Local administration of HMWH has been shown to reduce the infiltration of immune cells in a rodent model of radicular pain postlaminectomy, 15 suggesting a potential use in surgical settings.…”
Section: Other Potential Targets For High-molecularweight Hyaluronanmentioning
confidence: 99%